Association Between Plasma Exosomes S100A9/C4BPA and Latent Tuberculosis Infection Treatment: Proteomic Analysis Based on a Randomized Controlled Study - Du, Ying; Xin, Henan; Cao, Xuefang; Liu, Zisen; He, Yijun; Zhang, Bin; Yan, Jiaoxia; Wang, Dakuan; Guan, Ling; Shen, Fei; Feng, Boxuan; He, Yongpeng; et al. (Frontiers in Microbiology, 2022)
Background: Identifying host plasma exosomes proteins associated with host response to latent tuberculosis infection (LTBI) treatment might promote our understanding of tuberculosis (TB) pathogenesis and provide useful tools for implementing precise intervention. Methods: Based on an open-label randomized controlled trial (RCT) aiming to evaluate the short-course regimens for LTBI treatment, plasma exosomes from pre- and post- LTBI treatment were retrospectively detected by Label free quantitative protein mass spectrometry and validated by parallel reaction monitoring method for participants with changed or not changed infection testing results after LTBI treatment. Eligible participants for both screening and verification set were randomly selected from the based-RCT in a 1:1 ratio by age and gender. The IFN-γ level decreasing from > 0.70 IU/ml before treatment to < 0.20 IU/ml within one week after treatment was defined as reversion. The predictive ability of the candidate proteins was evaluated by receiver operating characteristic (ROC) analysis. Results: Totally, two sample sets for screening (n=40) and validation (n=60) were included. Each of them included equal number of subjects with persistent positive or reversed QuantiFERON-TB Gold In-Tube (QFT) results after LTBI. A total of 2321 exosome proteins were detected and 102 differentially expressed proteins were identified to be associated with QFT reversion. Proteins with high confidence and original values intact were selected to be further verified. Totally, 9 downregulated proteins met the criteria were validated. After verification, C4BPA and S100A9 were confirmed to be still significantly downregulated (fold change < 0.67, p < 0.05). The respective area under the ROC curve were 0.73 (95% CI: 0.57-0.89) and 0.69 (95% CI: 0.52-0.86) for C4BPA and S100A9 with a combined value of 0.78 (95% CI: 0.63-0.93). The positive and negative predictive values for combined markers were 70.10% (95% CI: 50.22%-86.30%) and 55.63% (95% CI: 29.17%-61.00%). Conclusion: Our findings suggested that downregulated C4BPA and S100A9 in plasma exosomes might be associated with host positive response to LTBI treatment. Further studies are warranted to verify the findings and potentially underlying mechanisms in varied populations with larger sample size.